Epidemiological Study of Anemia in Diyala Province / Iraq (Diyala Journal of Medicine, 2021)
Background: More than one billion people worldwide are affected with anemia. Studies have shown that nutritional deficiency, particularly a decrease in iron-rich food consumed, seems to be the most common cause of anemia. Objective: To study some demographic characteristics of anemia in children of different residencies of Diyala governorate/ Iraq. Patients and Methods: A cross-sectional descriptive study piloted in Al-Batool Teaching hospital in Baqubah / Diyala- Iraq from February 1st to Sept 30th 2019. Children was categorized according to the residency into two groups (rural & urban regions), anemia was sorted according to WHO classification: normal Hb 11 gm/dL, mild anemia 10- 10.9 gm/dL, moderate 7- 9.9 gm/ dL, and severe anemia Hb < 7 gm/dl. Results: One hundred seventeen children aged 6 months – 9 years were included in the study; 58.1% males and 41.9% females, 104 children 88.9% were less than 3.5 years, and 13 (11.1% ) children of 3.5 years and more. Sixteen children 13.7% were having normal Hb level and the remaining was anemic as follow: 35.9% mild anemia, 46.1% moderate anemia, 4.3% severe anemia, p-value 0.000. It was found that 57.3% of children belongs to family lived in urban areas, while 50 (42.7%) of them live in rural areas. The number of children who had moderate anemia was more in rural areas, p-value 0.008. Conclusion: Most of the studied children had a moderate degree of anemia and this might be due to many factors, including a residency in rural areas.